Factors influencing citations to systematic reviews in skin diseases: a cross-sectional study through Web of Sciences and Scopus - Juan Manriquez; Karina Cataldo; Isidora Harz (Sociedade Brasileira de Dermatologia, 2015)
AbstractBACKGROUND:Disseminating information derived from systematic reviews is a fundamental step for translating evidence into practice.OBJECTIVE:To determine which features of dermatological SR are associated with systematic review dissemination, using citation rates as an indicator.METHODS:Dermatological systematic reviews published between 2008 and 2012 were obtained from Scopus, the ISI Web of Sciences and the Cochrane Skin Group. Bibliometric data of every systematic review were collected and analyzed.RESULTS:A total of 320 systematic reviews were analyzed. Univariable analysis showed that the journal impact factor, number of authors, and total references cited were positively associated with the number of citations. There was a significant difference in the median number of citations with regard to the corresponding author's country, type of skin disease, type of funding, and presence of international collaboration. Cochrane reviews were significantly associated with a lower number of citations. Multivariable analysis found that the number of authors, number of references cited and the corresponding author from United Kingdom were independently correlated with many citations. Cochrane systematic reviews tended to be independently associated with a lower number of citations.CONCLUSIONS:Citation number to systematic reviews may be improving by increasing the number of authors, especially collaborative authors, and the number of cited references. The reasons for the association of Cochrane SRs with fewer citations should be addressed in future studies.